Depressed mood enhances anxiety to unpredictable threat - Robinson, OJ (2011)
BACKGROUND: Depression and anxiety disorders (AD) are highly comorbid, but the reason for this comorbidity is unclear. One possibility is that they predispose one another. An informative way to examine interactions between disorders without the confounds present in patient populations is to manipulate the psychological processes thought to underlie the pathological states in healthy individuals. In this paper we therefore asked whether a model of the sad mood in depression can enhance psychophysiological responses (startle) to a model of the anxiety in AD. We predicted that sad mood would increase anxious anxiety-potentiated startle responses. METHODS: In a between-subjects design, participants (N=36) completed either a sad mood induction procedure (N=18) or neutral mood induction procedure (N=18). Startle responses were assessed during short duration predictable electric shock conditions (fear-potentiated startle) or long-duration unpredictable threat of shock conditions (anxiety-potentiated startle). RESULTS: Induced sadness enhanced anxiety-, but not fear- potentiated startle. CONCLUSIONS: This study provides support for the hypothesis that sadness can increase anxious responding measured by the affective startle response. This, taken together with prior evidence that AD can contribute to depression, provides initial experimental support for the proposition that AD and depression are frequently comorbid because they may be mutually reinforcing.